DIFFERENTIATING NARCISSISM AND MACHIAVELLIANISM IN PEOPLE ARTISTICALLY GIFTED AND WITH AVERAGE ARTISTIC SKILLS - ŁOPUSZAŃSKA, JULIA (Studia Psychologica: Theoria et praxis, 2016)
Narcissism and machiavellianism are two out of three components of the Dark Triad proposed by Paulhus and Williams. This construct is characterized by high intensification of certain features for example egoism and manipulatory tendencies. The goal of this study was to find if people with artistic skills differ from those without any artistic skills in intensification of machiavellistic and narcissistic traits. The study was undertaken on 141 adults from which 74 were students of The Academy of Fine Arts and 67 were students of other Universities not associated with art. Study was conducted using Narcissistic Personality Inventory (NPI) by Ruskin and Hall in polish adaptation by Bazińska and Drat-Ruszczak and Mach IV Scale by Christie and Geis to analyze machiavelistic attitude. Results indicate that art skills are factor that significantly differs level of evaluated traits. Subjects with artistic skills have higher level of machiavelistic and narcissistic traits in comparison to subjects without such skills. Furthermore results have shown that not only the fact of having art skills matters but also conviction of oneself artism.